Competition between nucleation and confinement in the crystallization of poly(ethylene glycol)/ large aspect ratio hectorite nanocomposites. (12th August 2020) - Habel, Christoph; Maiz, Jon; Olmedo-Martínez, Jorge L.; López, Juan V.; Breu, Josef; Müller, Alejandro J.
Abstract: The overall crystallization kinetics of polymer nanocomposites is determined by nucleation and crystal growth, both of which are greatly affected by confinement. Heterogeneous nucleation is influenced by the interphase area between filler and polymer matrix. Starting with a homogeneous lamellar lyotropic aqueous dispersion of a mixture containing polyethylene glycol (PEG) and varying amounts of a high aspect ratio layered silicate (hectorite, Hec), nanocomposite films were casted containing a systematic variation of the degree of PEG confinement. This is achieved by a partial phase segregation upon drying, where independent of filler content, a thermodynamically stable, 1-dimensional crystalline hybrid with a constant volume of intercalated PEG (0.81 nm corresponding to a fraction of 75 wt% and 55 vol%, respectively) is formed. This intercalated hybrid phase is incorporated into segregated PEG domains. The kinetics of the thermodynamically driven segregation is dependent on the PEG volume available in surplus of the hybrid. Due to the very large lateral extension of the Hec, the segregated domains are increasingly two dimensional. As evidenced by transmission electron micrographs and powder X-ray diffraction, the segregation produces composite structures where, in dependency of filler content, PEG slabs of different thickness are separated by domains of the intercalated hybrid material. The crystallization behavior of these bi-phasic materials was investigated by Differential Scanning Calorimetry (DSC) and Polarized Light Optical Microscopy (PLOM). DSC results reveal a competition between the nucleating effect of Hec, which was particularly important at low amounts, and the confinement of PEG at higher filler loadings. Applying a self-nucleation protocol, the nucleation efficiency of the hectorite was shown to be up to 67%. The isothermal crystallization kinetics accelerated at low Hec contents (nucleation) up to a maximum, and then decreased as Hec content increased (confinement). Additionally, a clear correlation between filler content and the Avrami index was obtained supporting the increase in confinement as filler loading increased. Graphical abstract: The influence of a high aspect ratio layered silicate onto the crystallization kinetics of polyethylene glycol (PEG) was investigated. Systematic variation of the filler content allows tuning the nanocomposite structure and study the competition of nucleation and confinement. Image 1 Highlights: Lamellar lyotropic aqueous dispersions of PEG/high aspect ratio Hec were prepared. The isothermal crystallization kinetics went through a maximum with HEC addition. A clear correlation between filler content and the Avrami index was obtained. Competition between nucleation and confinement in PEG/Hec nanocomposites was found.